Trauma Care Pre-Hospital Manual - Greaves, Ian; Porter, Keith; Wright, Chris; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This new book provides evidence based guidelines for the immediate clinical management of major trauma.It has been written by clinicians with many years of trauma experience, and endorsed as authoritative by Trauma Care (UK)The UK now has highly effective trauma systems. Clinical developments include the introduction of damage control resuscitation, tranexamic acid, blood product resuscitation, novel hybrid resuscitation and an emphasis on the control of major external haemorrhage as part of a new ABCDE approach. Consequently, more individuals with major trauma are surviving than ever before. Optimal pre-hospital care is essential for improved survival rates and reduced morbidity.
IntroductionAcknowledgements Abbreviations and acronyms Contributors 1. Trauma: A global perspective 2. Safety 3. The incident scene 4. Communication in pre-hospital care 5. Mechanism of injury 6. The primary survey 7. Catastrophic haemorrhage 8. Airway management 9. Chest injuries 10. Shock 11. Entrapment and extrication 12. Head injury 13. Spinal injuries 14. Musculoskeletal trauma 15. Analgesia, sedation and emergency anaesthesia 16. The injured child 17. Trauma in pregnancy 18. Trauma in the elderly 19. Burns 20. Firearms, ballistics and gunshot wounds 21. Blast injuries 22. Trauma management in the austere pre-hospital environment 23. Mass casualty situations 24. Retrieval and transport 25. Handover and documentation 26. Law and ethics in pre-hospital care 27. Research and audit in pre-hospital care 28. Training in pre-hospital emergency medicine (PHEM) 29. Trauma systems Annex A Practical procedures in thoracic trauma Annex B Traumatic cardiac arrest Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: MEDICAL / Clinical Medicine; emergency response; evidence based practice; major trauma; practice guidelines; trauma education; trauma management; Wounds and injuries -- Nursing; Advanced Trauma Life Support Care; Wounds and Injuries -- therapy; Electronic books